Islamic calendar anomalies: Pakistani practitioners' perspective. (5th February 2018) - Halari, Anwar; Helliar, Christine; Power, David M.; Tantisantiwong, Nongnuch
Abstract : Purpose: Studies on Islamic calendar anomalies in financial markets tend to apply quantitative analysis to historic share prices. Surprisingly, there is a lack of research investigating whether the participants of such markets are aware of these anomalies and whether these anomalies affect their investment practice. Or is it a case that these practitioners are completely unaware of the anomalies present in these markets and are missing out on profitable opportunities? The purpose of this paper is to analyse the views of influential participants within the Pakistani Stock Market. Design/methodology/approach: The study documents the findings for 19 face-to-face semi-structured interviews conducted with brokers, regulators and high-net-worth individual investors in Karachi. Findings: The paper's major findings indicate that the participants believed that anomalies were present in the stock market and market participants were actively attempting to exploit these anomalies for abnormal gains. Interviewees suggested that predictable patterns can be identified in certain Islamic months (Muharram, Safar, Ramadan and Zil Hajj). The most common pattern highlighted by the interviews related to the month of Ramadan. Furthermore, interviewees mentioned the influence of the "Memon" community in the Pakistani Stock Market. Respondents also suggested that investor sentiment played an important role in influencing the stock market prices and trading patterns. Originality/value: Because all the prior studies investigating Islamic calendar anomalies in Muslim-majority countries adopted quantitative method using secondary data, the current investigation is of particular value, as it focuses on the qualitative analyses and reports the views of market participants. This allows to fully explore the topic under investigation and to draw robust conclusions.